2014
DOI: 10.1177/1350506814549424
|View full text |Cite
|
Sign up to set email alerts
|

Local women’s coalitions: Critical actors and substantive representation in Spanish municipalities

Abstract: The relationship between descriptive representation and substantive representation is an issue that has been widely discussed by women's studies scholars. In general, it is assumed that there exists a positive relationship between the two, but the literature and empirical analysis show that substantive representation also depends on the action of other critical actors, such as gender agencies and the women's social movement. Comparative research has shown the existence of a common pattern in post-industrial de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 46 publications
0
9
0
2
Order By: Relevance
“…Gender equality in local government is another factor that could influence financial sustainability. Previous studies (Jennings, 1983; Rodríguez-Garcia, 2015) found that men had a higher level of political engagement and were more active managers than women. In parallel, following McGregor’s (1960) theory that the management style of women leaders is different and motivated towards common interest, women have been found to show more empathy for social problems, and hence reduce financial sustainability (Fox and Schuhmann, 1999; Ryan et al , 2005).…”
Section: The Financial Sustainability In Local Governmentsmentioning
confidence: 87%
“…Gender equality in local government is another factor that could influence financial sustainability. Previous studies (Jennings, 1983; Rodríguez-Garcia, 2015) found that men had a higher level of political engagement and were more active managers than women. In parallel, following McGregor’s (1960) theory that the management style of women leaders is different and motivated towards common interest, women have been found to show more empathy for social problems, and hence reduce financial sustainability (Fox and Schuhmann, 1999; Ryan et al , 2005).…”
Section: The Financial Sustainability In Local Governmentsmentioning
confidence: 87%
“…Projects also include actions to foster gender roles changes to facilitate compatibility between public space incorporation and the traditional care role within the home. Although the difference between URBAN and URBANA initiatives is small, the gender approach seems to be expanded in the later, either because work/life balance is explicitly one of its objectives or because of equality policies trends in Spain, as well as the critical actors that drive them at the local level [64,71]. This outcome points to the role that integrated urban development interventions can play concerning gender inequalities in local welfare systems, not just because of their attention to the classic inequalities that women face, but particularly because of their contribution to the development of defamilisation processes.…”
Section: Discussionmentioning
confidence: 99%
“…[61,62]. Although gender mainstreaming is not common in local governments [63], they have increasingly incorporated equality agencies and plans, albeit with differences according to the role played by critical actors and women's coalitions that promote the inclusion of gender issues in the municipal agenda [64].…”
Section: Methodsmentioning
confidence: 99%
“…Among the different levels of public administration, local governments offer more opportunities to implement and evaluate the impact of the “balanced presence of women and men” in the public sector. The large number of politicians in Spanish local governments (67,515 representatives chosen in the 2015 municipal elections), their proximity to citizens and the provision of services related to women's preferences (Rodríguez‐García, 2015) make local governments the ideal context to assess the substantive representation of women in public services. One of the services where this impact can best be measured is welfare services, and more specifically, the protection of vulnerable groups in society (children, the elderly, the disabled, immigrants, etc.…”
Section: Introductionmentioning
confidence: 99%